The Polyanalgesic Consensus Conference (PACC): Recommendations for Trialing of Intrathecal Drug Delivery Infusion Therapy. Issue 2 (2nd January 2017) - Deer, Timothy R.; Hayek, Salim M.; Pope, Jason E.; Lamer, Tim J.; Hamza, Maged; Grider, Jay S.; Rosen, Steven M.; Narouze, Samir; Perruchoud, Christophe; Thomson, Simon; Russo, Marc; Grigsby, Eric; et al.
Abstract : Introduction: Intrathecal (IT) drug infusion is an appropriate and necessary tool in the algorithm to treat refractory cancer and noncancer pain. The decision‐making steps/methodology for selecting appropriate patients for implanted targeted drug delivery systems is controversial and complicated. Therefore, a consensus on best practices for determining appropriate use of IT drug infusion may involve testing/trialing this therapy before implantation. Methods: This current Polyanalgesic Consensus Conference (PACC) update was designed to address the deficiencies and emerging innovations since the previous PACC convened in 2012. A literature search identified publications available since the previous PACC publications in 2014, and relevant sources were contributed by the PACC members. After reviewing the literature, the panel determined the evidence levels and degrees of recommendations. The developed consensus was ranked as strong (>80%), moderate (50–79%), or weak (<49%). Results: The trialing for IT drug delivery systems (IDDS) remains an area of continued controversy. The PACC recommendations for trialing are presented in 34 consensus points and cover trialing for morphine, ziconotide, and medication admixtures; starting doses and titration practices; measurements of success; trial settings and monitoring; management of systemic opioids during trialing; and the role of psychological evaluation. Finally, the PACC describes clinical scenarios in which IT trialing is required or not required. Conclusion: The PACC provides consensus guidance on best practices of trialing for IDDS implants. In addition, the PACC recommends that no trial may be required in certain patient populations.